ANALISIS PERHITUNGAN ASET DAN LIABILITAS BERDASARKAN PENILAIAN STANDAR AKUNTANSI KEUANGAN DAN PRAKTEK AKUNTANSI ASURANSI PADA PT ASURANSI JIWA MEGA LIFE - Nurlatifah, Siti (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This research aims to (1) determine the amount of the difference between GAAP (Generally Accepted Accounting Principles) and SAP (Standar Accounting Practices) assessment and the amount of assets that are not allowed in the calculation of assets, (2) determine the amount of the difference between GAAP and SAP ratings in the calculation of liabilities PT Asuransi Jiwa Mega Life period in 2016 and (3) determine the value Risk Based Capital (RBC) associated with the achievement of the solvency ratio of PT Asuransi Jiwa Mega Life period in 2016. The research found that (1) the largest amount of funds needed to anticipate the risk of loss that may arise as a result of the deviation in the management of assets and liabilities is at Risk Liability Insurance (Schedule D) that is equal to 49.90% (Rp. 26,445.87 million) of the total number of RBC Rp. 52,996.63 million (2) the achievement of the solvency ratio achieved by the Life Insurance Company Megalife period of 2016 by 670%, meaning that if all customers to make a claim, the insurance company can meet all of its liabilities and still have a reserve of 570%.